Supramolecular architectures sustained by delocalised C–I···π(arene) interactions in molecular crystals and the propensity of their formation† - Tiekink, Edward R. T. * (Royal Society of Chemistry, 2020)
A systematic analysis of the Cambridge Crystallographic Database has been made for supramolecular architectures sustained by C–I···π(chelate ring) interactions where the iodide atom is directed towards the ring centroid, Cg, of the arene ring, i.e. with the angle subtended at the iodide atom, C–I···Cg (θ) being ≥ 160°. The majority of the 181 identified aggregates are one-dimensional chains of varying topology (100 examples) followed by zero-dimensional aggregates (71 examples) with only a small number of two-dimensional arrays (4 examples). The overall likelihood for the formation of these delocalised interactions is around 4%, a number that increases to around 15% when the angle θ restriction is relaxed to 90°. A comparison has been made with the formation of C–X···π(chelate ring) interactions for the lower (X =) bromide, chloride and fluoride congeners. This shows these interactions are more likely to form in the order X = I > Br > Cl >> F.